A creative journey developing an integrated high-fashion knitwear development process using computerized seamless v-bed knitting systems - Yang, Sooyung (Curtin University, 2010)
This PhD applied a participatory action research approach to address the organizational problems that compromise the use of computerized seamless V-bed knitwear systems in the high-fashion knitwear sector. The research is a response to a widely acknowledged conflict between high-fashion design processes and processes by which designs are developed on computerized seamless V-bed knitting systems. The social, organizational, and technical aspects of design and manufacturing using computerized seamless V-bed knitting technology in high-fashion knitwear design were analyzed as a socio-technical system (STS). This approach led to a review of the workflows, tasks and roles; identifying and testing new design and manufacturing processes, design methods, and garment solutions; creating a theory model of a new integrated design process; and developing and testing new design processes, design methods, and fashion design education courses that teach these new fashion knitwear approaches.The research was undertaken using a Shima Seiki WholeGarment® system, a current computerized seamless V-bed knitting design and manufacturing technology. The studio workspace, yarn, use of the Shima Seiki system; involvement in fashion projects, and associate supervision were provided by the Department of Agriculture and Food Western Australia (DAFWA).The research demonstrated a high-fashion knitwear designer can undertake all aspects of managing computerized seamless V-bed knitwear design and production to the completion of 1st sample, the first successful sample of a new fabric or garment, was produced using the computer knit data. This finding was developed into a new integrated design process and design methods that remove most of the problems of computerized seamless V-bed knitting systems in high-fashion and offers additional benefits including reduction in time to market and design costs, and increases in the creative solution space for high-fashion knitwear design.The researcher has called this new role, a ‘designer-interpreter’ to denote a professional knitwear designer with additional training in managing computerized seamless knitting machines. Within the context of ‘designer-interpreter’, this research also established the feasibility of a new form of a ‘post-industrial craft-based one-person knitwear production system’.